Optimalisasi Leadership Transformation Melalui Digital Attendance dan Sistem Informasi Manajemen pada Kantor Urusan Agama (KUA) Kabupaten Mamuju Tengah - Widiyastutin, Dewi; Yeni, Hari (Humanities Studies, Post-Graduate Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
This study examined how the Office of Religious Affairs (KUA) of Central Mamuju Regency optimizes leadership transformation by using an attendance information system and digital management. Functional officials, implementing officials, and other administrative staff comprise this quantitative study population. A proportional random sampling approach was used, and the study's sample size consisted of 30 respondents. Questionnaires are created and distributed to respondents to collect data. T-test, F-test, and multiple linear regression techniques were used to examine the questionnaire data. The findings of this study are as follows: (1) The measure of leadership transformation is greatly influenced by digital presence. (2) Management information systems positively influence leadership transformation indicators. (3) Integrating digital attendance and management information systems contributes significantly to improving decision-making processes within the organization. (4) Leadership transformation in a digital context requires fostering adaptability, encouraging collaboration, and utilizing technological advancements to drive efficiency. (5) The successful adoption of digital tools in leadership transformation leads to enhanced performance management, improved accountability, and increased operational transparency. (6) Organizational effectiveness is significantly impacted by the integration of technology-driven management systems, leading to higher efficiency and better service delivery. These results highlight the importance of digitalization in enhancing leadership effectiveness and optimizing organizational management in government institutions. This study contributes to understanding how digital transformation supports leadership development and administrative efficiency, providing valuable insights for policymakers and organizational leaders to implement digital solutions effectively.